Diagnostic significance of combining D-dimer with high-sensitivity cardiac troponin I for improving the diagnosis of venous thromboembolism in the emergency department: Troponin for diagnosing venous thromboembolism - Bonfanti, Laura; Cervellin, Gianfranco; Calamai, Simone; Lunian, Marco; Aloe, Rosalia; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background. Although cardiac troponins are valuable tools for risk stratification in patients with venous thromboembolism (VTE), their significance remains elusive in diagnosing venous thrombosis. Methods. D-dimer (age-adjusted cut-off) and high-sensitivity cardiac troponin I (HS-cTnI; reference limit, <10.5 ng/L in women and <17.8 ng/L in men) were measured in 2199 consecutive patients (1106 women and 1093 men; mean age, 63±20 years), admitted to the Emergency Department of the University Hospital of Parma during a 3-month period. Overall, 53 patients were finally diagnosed with VTE (12 with deep vein thrombosis and 41 with pulmonary embolism). Results. The diagnostic performance (area under the curve; AUC) of D-dimer and HS-cTnI was 0.70 and 0.71 for all VTE episodes, 0.70 and 0.63 for deep vein thrombosis (DVT), 0.70 and 0.74 for pulmonary embolism (PE), respectively. The combination of positive values of both biomarkers yielded better diagnostic performance than D-dimer values alone for diagnosing PE (AUC, 0.80; p<0.001 vs. D-dimer alone), but not for diagnosing DVT (AUC, 0.73; p=0.458 vs. D-dimer alone). In patients with PE, positive HS-cTnI values in patients with concomitantly positive D-dimer values yielded identical diagnostic sensitivity compared to D-dimer positivity alone (i.e., 1.00), but nearly double diagnostic specificity (i.e., 0.71 vs. 0.40). Positive HS-cTnI values (AUC, 0.68), but not D-dimer positivity (AUC, 0.51), were associated with 30-day hospital readmission of VTE patients. Conclusions. The results of this study open intriguing opportunities for combining HS-cTnI and D-dimer in the diagnostic approach of patients with PE.